Application of natural dye from beka bark for fashion products / Muhammad Amirul Zuber and Habibah Hj. Abd Jabbar - Zuber, Muhammad Amirul; Abd Jabbar, Hj., Habibah (Universiti Teknologi MARA, 2021)
This research highlighted the application of natural dye from Beka bark for fashion products. Beka bark can produce excellent yellow colour and can get a different shade of colour from the leaves, stems, and fruits. The local people do not know that these fruits can produce a stunning and unique natural colour. Also, local people nowadays only know that Beka bark is known as a herb and can be used as traditional medicine. Other than that, the naturally dyed fabric has a big competition with synthetic materials from its vibrant colours to the cost of producing the fabric. However, this study was to determine the effect of mordant on natural dyeing with Beka bark. Thus, this project aims to investigate the type of fabric that shows the Beka bark dye colour. Also, to produce fashion products from naturally dyed fabrics. Other than that, combine naturally dyed fabric into a fashionable product. Therefore, the methodology used in this study is an experimental method. The experimental method involves the manipulation of variables to establish cause and effect. The researcher must collect data through the experiment process and literature studies to understand fashion products using natural dye from Beka bark. Observations on the outcome and process of fashion products are also crucial in this study. The information collected will be used during the visual production process for the final project. However, the effectiveness may depend on the researcher's skills, abilities, and knowledge to produce fashion products using natural dyeing from Beka bark. Natural dyeing also benefits society to give a better understanding of fashion products using natural dye from plants that save the environment from environmental pollution. This understanding not only helps artists be creative but also helps facilitate the search for materials from natural plants.